Dynamics of dissolved silicon in a large mesotrophic reservoir in south-central Indiana, U.S.A - Sethna, Lienne R.; Rasnake, Lindsey M.; Powers, Sarah R.; Plechaty, Zoe I.; Pouchak, Ariel H.; Hobbs, William O.; Royer, Todd V. (Frontiers in Environmental Science, 2025)
River damming disturbs the transport and fate of nutrients, which alters biogeochemical cycling within reservoirs and alters the flux of nutrients downstream. In reservoirs, silicon (Si) is retained in larger proportions relative to nitrogen (N) and phosphorus (P) which can reduce dissolved Si (DSi) availability and push phytoplankton communities to be dominated by non-siliceous, potentially harmful taxa, such as cyanobacteria. Lake Monroe is the largest reservoir in Indiana and provides drinking water for more than 140,000 people, making it a critical water resource and exemplar for potential Si retention within the Mississippi River basin. To quantify the retention of DSi in Lake Monroe, we calculated an annual DSi budget using measured DSi inputs and outputs between April 2020 and March 2021. We also measured in-lake DSi and phytoplankton community composition between May and October 2020 as well as long-term biogenic Si fluxes to the sediment to better quantify the mechanisms controlling DSi retention. We found that Lake Monroe retained over half of its annual DSi inputs over the monitoring period and that retention was driven by diatom growth and sedimentation. As the construction of large dams continues globally, it is important to quantify how the biogeochemical cycling and transport of DSi is changing and the role of reservoirs in potentially shifting diatoms from N- or P- limited to Si-limited.